2020
DOI: 10.1021/acsabm.9b01077
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate-Encapsulated Electrospun Polycaprolactone-Based Composite Scaffolds for Osteoporotic Bone Defect Repair

Abstract: Bone fractures associated with osteoporosis are a major concern all over the world especially among the elderly population and postmenopausal women. Bisphosphonates (BPs) are widely used clinically for both treatment and prevention of osteoporosis despite their poor oral bioavailability and undesired side effects. Local delivery of BPs from polymeric scaffolds can improve the efficacy and overcome the undesirable side effects associated with oral bisphosphonate therapy. The aim of the present study is to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Rajan et al used electrostatic spinning technology to load pamidronate into polycaprolac-tone/polycaprolactone-polyethyleneglycol-polycaprolactone/n-HAp (PCH) scaffold, and the study confirmed that PDS in the composite scaffolds was well-released in phosphate buffer. The PCH scaffolds incorporating 3 wt % PDS can effectively promote the bone healing of calvarial defects in osteoporotic rats [ 166 ]. Alendronate is a nitrogen-containing bisphosphonate.…”
Section: Drug-loaded N-hap Composite Scaffoldsmentioning
confidence: 99%
“…Rajan et al used electrostatic spinning technology to load pamidronate into polycaprolac-tone/polycaprolactone-polyethyleneglycol-polycaprolactone/n-HAp (PCH) scaffold, and the study confirmed that PDS in the composite scaffolds was well-released in phosphate buffer. The PCH scaffolds incorporating 3 wt % PDS can effectively promote the bone healing of calvarial defects in osteoporotic rats [ 166 ]. Alendronate is a nitrogen-containing bisphosphonate.…”
Section: Drug-loaded N-hap Composite Scaffoldsmentioning
confidence: 99%
“…Poly­(ε-caprolactone) is widely applied in long-term surgical implants and slow-releasing drug-delivery systems due to its biocompatibility, biodegradability, and suitable mechanical properties. In tissue engineering, PCL has been studied for applications that require slowly degrading materials, for example, guided bone regeneration and vascular grafts. Researchers have also explored ways to modify PCL to increase its degradation rate. , One approach is to make copolymers or to blend PCL with other polymers, such as polylactic acid, poly­( N -(2-hydroxypropyl)­methacrylamide), alginate, , starch, , and zein . However, blending polymers can result in phase separation, degrading the mechanical properties of the resulting material. , In addition, blending may lead to loss of the desired characteristics of the original system, such as solubility, biocompatibility, mechanical properties, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The production of fibroporous membranes via the electrospinning technique has turned into an area of extensive research with the potential of fabricating commercial products on a large scale . The large surface area-to-volume ratio of the electrospun membrane is a favorable attribute for drug delivery applications, tissue repair, biological dressing, enzyme immobilization, etc. , The versatility of the technique lies in the fact that different processing modifications are possible with it including multiple fluid processing like co-axial electrospinning, side-by-side electrospinning, tri-axial electrospinning, , etc. Recently, fabrication of fibrous membranes with “smart” properties is gaining much attention also .…”
Section: Introductionmentioning
confidence: 99%